Which Ladder to Climb? Wages of Workers by Job, Plant, and Education - Christian Bayer; Moritz Kuhn (Institute of Labor Economics (IZA), 2018)
Wages grow but also become more unequal as workers age. Using German administrative data, we largely attribute both life-cycle facts to one driving force: some workers progress in hierarchy to jobs with more responsibility, complexity, and independence. In short, they climb the career ladder. Climbing the career ladder explains 50% of wage growth and virtually all of rising wage dispersion. The increasing gender wage gap by age parallels a rising hierarchy gap. Our findings suggest that wage dynamics are shaped by the organization of production, which itself likely depends on technology, the skill set of the workforce, and labor market institutions.
Keywords: D33; E24; J31; 330; human capital; life-cycle wage growth; wage inequality; careers